1D Hexagonal HC(NH2)2PbI3 for Multilevel Resistive Switching Nonvolatile Memory. (17th July 2018) - Yang, June‐Mo; Kim, Seul‐Gi; Seo, Ja‐Young; Cuhadar, Can; Son, Dae‐Yong; Lee, Donghwa; Park, Nam‐Gyu
Abstract: Organic–inorganic halide perovskite is regarded as one of the potential candidates for next generation resistive switching memory (memristor) material because of fast, millivolt‐scale switching, multilevel capability, and high On/Off ratio. Here, resistive switching property of HC(NH2 )2 PbI3 (FAPbI3 ) depending on structural phase is reported. It is found that 1D hexagonal FAPbI3 (δ‐FAPbI3 ), formed at relatively low temperature, is active in memristor, while 3D trigonal FAPbI3 (α‐FAPbI3 ), formed at temperature higher than 150 °C, is inactive. Failure of switching from low resistance state to high resistance state is found for α‐FAPbI3, while δ‐FAPbI3 shows stable switching behavior. Density functional calculation reveals that iodine cluster in isotropic 3D α‐FAPbI3 is so stable after forming filament that the filament is hard to be ruptured at off state. However, for anisotropic δ‐FAPbI3, iodine cluster is not stable and migration barrier is much lower for c ‐axis (0.48 eV) than forab ‐plane (0.9 eV), which is beneficial for switching. The memristor devices based on δ‐FAPbI3 demonstrate endurance up to 1200 cycles with On/Off ratio (>10 5 ), retention time up to 3000 s, multilevel storage capacity, and working even at 80 °C. Abstract : Resistive switching of FAPbI3 depends on the crystal structure of FAPbI3 . Trigonal α‐FAPbI3 formed at high temperature doesn't show bipolar resistive switching, while resistive switching occurs repetitively for hexagonal δ‐FAPbI3 formed at low temperature. Dependence of resistive switching on crystal structure is related to migration of iodine vacancy in SET process and interaction energy of iodine vacancy in RESET process.